Hospitalisations for maternal assault are associated with increased risk of child protection involvement. (September 2019) - Orr, Carol; Fisher, Colleen; Sims, Scott; Preen, David; Glauert, Rebecca; O'Donnell, Melissa
Abstract: Background: Previous research shows a co-occurrence between children's exposure to violence and child maltreatment. Objective: This study examined the risk of maltreatment allegations in children whose mothers had been hospitalised due to an assault. Participants and setting: The study used a retrospective cohort of children born in Western Australia between 1990–2009 (N = 524, 534) using de-identified linked-administrative data. Methods: Multivariate Cox regression determined the adjusted and unadjusted hazard ratios for child maltreatment allegation in children with a mother hospitalised for assault. Models were adjusted for a range of sociodemographic characteristics. Results: One in five children had a maltreatment allegation following their mother's hospitalisation for assault. This increased to two in five children when the mother was assaulted in the prenatal period. Aboriginal children accounted for 57.6% of all allegations despite representing only 7.8% of the population. Children whose mother had a hospitalisation for assault were nine-times (HR = 9.20, 95%CI: 8.98–9.43) more likely to have a subsequent maltreatment allegation than children whose mother did not have a hospitalisation for assault. Following adjustment for confounding factors, both Aboriginal and non-Aboriginal children had an almost two-fold increased risk of maltreatment allegation (HR = 1.56, 95%CI: 1.43–1.70; HR = 1.93 95%CI:1.80–2.07). Conclusions: Our study shows that child maltreatment allegation is common in children following a maternal hospitalisation for assault. Targeted early intervention is required for families with young children, and pregnant women experiencing violence. Importantly service staff need awareness of the impact of violence on families and the appropriate services to refer families to.